UJI AKTIVITAS ANTIDIABETES KOMBINASI GLIBENKLAMID DAN EKSTRAK DAUN SALAM (Syzygium polyanthumWight.) TERHADAP MENCIT (Mus musculus) YANG DIINDUKSI ALOKSAN - Steffi Liem; Yuliet Yuliet; Akhmad Khumaidi (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2015)
Pharmacological therapy of Diabetes Mellitus (DM) is to use antidiabetic oral. Herbal medicine are also often used as an alternative treatment by patients. Even in some cases found patients combine drugs and herbal medicine to speed up the healing of DM. This study aims to know the effects of a combination of glibenclamide and bay leaf ethanol extract (BLEE) to decrease blood glucose levels and to determine its optimal combination dose as antidiabetic. The method was inducted alloxan at dose of 120 mg/kg BW intraperitoneally. The animal test used were mice which divided into 8 groups of tests, the negative control (Na CMC 0,5 %), positive control (glibenclamide 0,65 mg/kg BW), combination 1(glibenclamide+BLEE 250 mg/kg BW), combination 2 (glibenclamide+BLEE 500 mg/kg BW), combination 3 (glibenclamide+BLEE 750 mg/kg BW), BLEE 1 (250 mg/kg BW), BLEE 2 (500 mg/kg BW), and BLEE 3 (750 mg/kg BW). After 14 days study, data were analyzed by ANOVA showed the difference in decrease of blood glucose levels combination 2 (230±23,69) mg/dL and combination 3 (233,75±9,93) mg/dL were significantly different to the negative control (4±6,82) mg/dL, positive control (150,75±11,34) mg/dL, combination 1 (170±10,51) mg/dL, BLEE 1 (134,5±4,61) mg/dL, BLEE 2 (151,25±6,72) mg/dL, and BLEE 3 (158,75±17,64) mg/dL. While combination 2 and combination 3 were not significantly different. Combination of glibenclamide and bay leaf ethanol extract decreased blood glucose levels greater than a single dosage glibenclamide or bay leaf extract. Optimal doses decreased blood glucose levels was combination 2.